Definition and use of functional analogues in planetary exploration. (March 2021) - Foucher, F.; Hickman-Lewis, K.; Hutzler, A.; Joy, K.H.; Folco, L.; Bridges, J.C.; Wozniakiewicz, P.; Martínez-Frías, J.; Debaille, V.; Zolensky, M.; Yano, H.; Bost, N.; et al.
Abstract: The practical limitations inherent to human and robotic planetary exploration necessitate the development of specific protocols and methods. This non-standard approach requires testing and validation phases in order to optimise instrumental setups and improve data interpretation; this can occur prior to, during, or even after a mission. Flight instruments, and/or their spare models, may be evaluated using relevant terrestrial materials and/or locations. These materials are called analogues: "analogue sites" for large-scale locations, and "analogue samples" for smaller-scale materials. Depending on the scientific domain, the word "analogue" may carry different meanings but is invariably used to denote objects having compositions and/or physical properties similar to specific extraterrestrial objects. However, due to the variability in composition and properties of natural materials, there are always – inevitably – some differences between the analogue and the object(s) to which it refers. In analogue studies, it is, thus, important to focus on the specific properties that need to be imitated and to consider analogue properties rather than analogue sites or samples alone. Here, we introduce the concept of "functional analogues". We first make an overview of the different types of analogues and sort them according to their utility. We then describe how different types of functional analogues can be used throughout the timeline of space missions, from the evaluation of different methods in the definition of a mission to understanding the results acquired by probes exploring extraterrestrial bodies. Finally, logical pathways are outlined that facilitate the selection of the best-suited functional analogue(s) according to their intended use and taking into account practical limitations. Highlights: There are inevitably some differences between an analogue and the object(s) to which it refers. "Functional analogues" are defined according to the specific properties that need to be imitated. Functional analogues are useful throughout the timeline of space missions (before, during and after). Logical pathways permit the selection of the best-suited functional analogue(s).